Problem-Based Learning in Improving Student Learning Outcomes in Biology Learning - Amirra Putri; Soesy Asiah Soesilawati; Neneng Diani (Universal Education, 2024)
This study explores the impact of the Problem-Based Learning (PBL) method on improving biology learning outcomes among high school students. Despite biology’s critical role in addressing global challenges, students often struggle with understanding basic biological concepts, leading to unsatisfactory academic performance. This research aimed to assess the effectiveness of PBL in enhancing students' biology comprehension. The study was conducted at SMAN 17 Bandung with 69 students as participants and utilized a one-group pretest-posttest design. Data were collected through a validated learning outcome test and analyzed using a paired sample t-test. The results indicated a significant improvement in students' post-test scores, with a mean difference of 38.88 points between the pretest and post-test and an N-gain of 0.703, categorized as high. These findings demonstrate that PBL significantly enhances students' understanding of biology by encouraging active engagement, critical thinking, and problem-solving. The study concludes that PBL is an effective learning method that improves biology learning outcomes, preparing students to become independent and collaborative problem solvers. However, challenges such as teacher readiness, time constraints, and limited resources must be addressed for broader implementation.